The Hobbit, or, There and Back Again - (John Ronald Reuel); Tolkien, J. R. R.; 1892-1973.; Lee, Alan (Boston, 2001)
Bilbo Baggins, a respectable, well-to-do hobbit, lives comfortably in his hobbit-hole until the day the wandering wizard Gandalf chooses him to take part in an adventure from which he may never return.
"Text of this edition is based on that first published in Great Britain by Collins Modern Classics in 1998 ... corrections have been made to that setting"--T.p. verso.
Keywords: Middle Earth (Imaginary place); Fiction; Fantasy